Efficacy of adjunctive inhaled colistin and tobramycin for ventilator-associated pneumonia: systematic review and meta-analysis (2024)
ABSTRACT: Introduction,Ventilator-associated pneumonia (VAP) presents a significant challenge in intensive care units (ICUs). Nebulized antibiotics, particularly colistin and tobramycin, are commonly prescribed for VAP patients. However, the appropriateness of using inhaled antibiotics for VAP remains a subject of debate among experts. This study aims to provide updated insights on the efficacy of adjunctive inhaled colistin and tobramycin through a comprehensive systematic review and meta-analysis. Methods A thorough search was conducted in MEDLINE, EMBASE, LILACS, COCHRANE Central, and clinical trials databases (www.clinicaltrials.gov) from inception to June 2023. Randomized controlled trials (RCTs) meeting specific inclusion criteria were selected for analysis. These criteria included mechanically ventilated patients diagnosed with VAP, intervention with inhaled Colistin and Tobramycin compared to intravenous antibiotics, and reported outcomes such as clinical cure, microbiological eradication, mortality, or adverse events. Results The initial search yielded 106 records, from which only seven RCTs fulfilled the predefined inclusion criteria. The meta-analysis revealed a higher likelihood of achieving both clinical and microbiological cure in the groups receiving tobramycin or colistin compared to the control group. The relative risk (RR) for clinical cure was 1.23 (95% CI: 1.04, 1.45), and for microbiological cure, it was 1.64 (95% CI: 1.31, 2.06). However, there were no significant differences in mortality or the probability of adverse events between the groups. Conclusion Adjunctive inhaled tobramycin or colistin may have a positive impact on the clinical and microbiological cure rates of VAP. However, the overall quality of evidence is low, indicating a high level of uncertainty. These findings underscore the need for further rigorous and well-designed studies to enhance the quality of evidence and provide more robust guidance for clinical decision-making in the management of VAP.